2018
DOI: 10.1177/2158244018764234
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Professional Development Strategies: A Model for the Iranian EFL Teachers’ Success

Abstract: Throughout the past decade, evaluating teachers' success has become a crucial issue due to the increased motivation on teacher accountability. In view of that the purpose of the present study is to determine EFL (English as a foreign language) teachers' success in the Iranian institutional context based on students' perspectives. More specifically, the present study surveyed any significant correlation between teachers' practices of continuing professional development (CPD) strategies and teachers' success. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Additional studies (e.g. Tabatabaee-Yazdi et al, 2018) have shown a significant correlation between teachers' personal continuing professional development strategies adopted by teachers and the development of teaching expertise. Research into personal developmental activity undertaken by practitioners (at times with degrees of institutional involvement as noted by Borg, 2018) have included mentoring (e.g.…”
Section: Language Teacher Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies (e.g. Tabatabaee-Yazdi et al, 2018) have shown a significant correlation between teachers' personal continuing professional development strategies adopted by teachers and the development of teaching expertise. Research into personal developmental activity undertaken by practitioners (at times with degrees of institutional involvement as noted by Borg, 2018) have included mentoring (e.g.…”
Section: Language Teacher Developmentmentioning
confidence: 99%
“…In this time, significant progress has been made in better understanding how and when learning takes place; however, much of the research has been conducted in the context of large-scale, formal professional development interventions, whether pre-service or in-service (Borg, 2015). Far less attention has been paid to those language practitioners 'taking charge of their own learning' (Wyatt & Ončevska Ager, 2017, p. 176), where developmental activity is primarily selected or initiated by teachers themselves and teachers' own development strategies play a central role (see, for example, Tabatabaee-Yazdi, Motallebzadeh, Ashraf, & Baghaei, 2018). This paper aims to provide insights into teacher learning in such contexts through a longitudinal study exploring practical knowledge growth in English language practitioners' teaching of speaking skills to migrants.…”
Section: Introductionmentioning
confidence: 99%
“…The Institute of Personnel and Development of the United Kingdom defines CPD as a constant keeping up-to-date (updating) of the professional knowledge throughout the entire working life through systematic, informal, or self-directed learning models (Refrigeri, 2018). However, unfortunately, for many teachers, CPD has been passive, one-shot workshops, designed by the administration and imposed on teachers for their implementation (Tabatabaee-Yazdi, Motallebzadeh, Ashraf, & Baghaei, 2018). Therefore, training aspects are instrumental in shaping the personality of a teacher.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This https: //doi.org/10.15405/epsbs.2020.01.5 Corresponding Author: Liliya V. Goryunova Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 37 process is based on the practicality oriented principle, which enables establishing conditions for constants teachers' development (Bourke, Lidstone, & Ryan, 2013). Another important direction in studies aimed at the search of more efficient system in further teacher training is creating various tools of evaluation of teachers success, designing a motivational system for teachers to develop professionally and constantly (Tabatabaee-Yazdi, Motallebzadeh, Ashraf, & Baghaei, 2018). Most activities in teachers' professional development in modern conditions of further training have tutoring technologies and portfolio as a basis.…”
Section: Introductionmentioning
confidence: 99%